PENINGKATAN RASA PERCAYA DIRI SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI ACTIVE LEARNING TIPE ACTIVE KNOWLEDGE SHARING DENGAN PENDEKATAN SAINTIFIK - Kamil, Nurdin; Jailani, Jailani (Profesi Pendidikan Dasar, 2018)
This study aims to describe the effect of the Active Knowledge Sharing model with the scientific approach to the self-confidence of fourth grade elementary school students. This research is a quasi-experimental research with pretest-posttest non-equivalent control group design design. This study used two experimental groups (Active Knowledge Sharing Model) and two control groups (ordinary learning). The population in this study consisted of an experimental group consisting of SDN Balangan 1 and SDN Sendangharjo, and the control group consisted of SDN Balangan 2 and SDN Kebonagung. Instruments used in collecting data in the form of non-test instruments in the form of a questionnaire to measure students' confidence level. Test data normality using Kolmogrov_Smirnov and homogeneity test using Box's M. Data test was analyzed using independent sample t-test. Result of Independent Sample t-test above, obtained by significance value of dependent variable of confidence sig. 0.05, ie 0.008 0.05. This means that H0 is rejected and Ha accepted, the conclusion is that there is a difference of influence between the experimental class and the control class on the student's self-confidence